Multiakad dalam Transaksi Syariah Kontemporer pada Lembaga Keuangan Syariah di Indonesia - Hasanudin Maulana (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
The development of Islamic finance in Indonesia affects the development of Islamic finance products dynamically. The agreement in Islamic transactions underwent a variety ofinnovations from several existing agreements in mu‘âmalah jurisprudence concept. One of them is the concept of multi-agreements in a transaction. Transactions with these multiagreement forms exist in almost Islamic products currently. This article also discusses various scholarly opinions with all variants of the concept multi-agreements.DOI: 10.15408/aiq.v3i1.2518